Threshold shift validity by documenting sensorineural acuity level: a useful tool for masking - Kapoor, Punnet; Zangmo, Nima; Garg, L. N.; Saini, Anu; Gupta, Manish (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Masking dilemma is a condition prevalent whenever there is significant hearing loss in non-test ear and conductive hearing loss in test ear resulting into narrow or non-existent plateau width. Three feasible ways are divulged to circumvent this condition namely, Sensorineural acuity level testing, Fusion Inferred at threshold and use of insert type transducers. Different circumstances encountered when using insert type transducers and Fusion Inferred at threshold test has made it peril to use. Thus, administration of sensorineural acuity level test has been preferred. Sensorineural acuity level test involves computation of individual threshold shifts and its comparison with normal threshold shifts when a maximum level of bone conducted noise is presented at the centre of forehead via bone conduction vibrator. This research study aims to document normal threshold shifts and its validation in individual with bilateral symmetrical sensorineural hearing loss. Methods: A prospective study was carried out among 50 normal individuals and 50 patients with bilateral symmetrical sensorineural hearing loss. Pertinent measures were taken to ensure fulfilment of all-inclusive and exclusive criteria. In addition, air conduction and bone conduction threshold were computed using conventional methods followed by administration of sensorineural acuity level test. Necessary comparison was made among the threshold shifts. Results: Inferences drawn showed closer correlation between sensorineural acuity level threshold and bone conduction thresholds during puretone audiometry. Conclusions: Sensorineural acuity level test has shown to be effectual in both rehabilitation and medical interventions. Besides, imperative role of an audiologist can be recognized in its administration and elucidation for better prognostication.